Iatrogenic injury of the ureter, urethra and bladder and methods of treatment [Iatrojenik ureter-mesane-uretra yaralanmalari ve tedavi yaklasimlari] - (:unkn) unknown (My University, 1999)
Iatrogenic urinary tract injury is a well-established potential complication of surgery for the benign and malignant diseases of the female pelvic organs. The ureters, bladder, or urethra ara at risk during all gynaecologic surgeries. While some injuries are recognizable intraoperatively, most are not immediately apparent and present only later with because of the common embryologic origin of the urinary tract and the female genital tract present a challenge to the surgeon. The present review briefly discusses the prevention, diagnosis, and management of iatrogenic urinary tract injuries in the female.
Keywords: Bladder; Iatrogenic trauma; Ureters; Urethra; Urologic complication